TI-RADS: to be or not to be. Polemic notes from the Eurasian Forum on thyroid cancer - Alexey V. Borsukov (Эндокринная хирургия, 2017)
Experts discussing about problems of ultrasound diagnostics of thyroid cancer in the format of TI-RADS and cytological Bethesda classification results at the Eurasian Forum of thyroid cancer are presented.